Ab initio Study on the Structural, Electronic and Optical Properties of Zn(1-x)MxS (M=Mn, Fe, Co, Cu) and Zn2SnO4 with Density Functional Theory - BONDAN FATHONI (NIM : 10511090), KRESNA
Structural, electronical and optical properties of ZnS and transition metal-doped (Mn, Fe, Co and Cu) ZnS was calculated with Full Potential Linearized Augmented Planewave (FP-LAPW) method within the Density Functional Theory (DFT) with exchange-correlation of modified Becke-Johnson potential to acquire accurate results. The main band gap of ZnS crystal is increased with the introduction of doping atom. Intermediate bands appear in the band gap due to the introduction of doping atom. Zn2SnO4 was also analyzed with the same method, in this case the distribution of Zn and Sn in the crystal was studied. Zn and Sn atoms can take place in the same site with 1:1 ratio leads to many possibilities of atomic distribution. According to the computational studies it was predicted that the possible distributions of Zn2SnO4 are layered or random. Layered distribution has direct band gap, on the other hand random distribution has indirect band gap. This information can be compared to the experimental data to determine wether the Zn or Sn atoms have layered or random distribution in the.